Determinants of cloud accounting adoption in Malaysian accounting practices: A user perspective - Azleen Ilias; Rahida Abd Rahman; Erlane K. Ghani; Kamaruzzaman Muhammad (Universiti Tenaga Nasional, 2025)
This study examines the factors that influence the intention to adopt cloud accounting among accounting practitioners in Malaysia, focusing on perceived ease of use, perceived usefulness, self-efficacy, perceived security, and competitive pressure. A quantitative approach was employed, with data collected through a survey distributed to accounting practitioners in audit and non- audit firms within the Klang Valley. A total of 136 valid responses were analyzed using correlation analysis to determine the relationships between the independent and dependent variables. The findings indicate that all five factors exhibit a significant positive correlation with the adoption of cloud accounting. The study highlights the growing importance of cloud technology in financial management, emphasizing the need for businesses and policymakers to improve cloud infrastructure support, address security concerns, and promote digital literacy among practitioners. While Malaysia continues to progress toward Industry 4.0, the findings suggest that further efforts are needed to improve cloud adoption readiness. The study offers valuable insights for organizations, policymakers, and academia to support the adoption of cloud technology, ensuring that Malaysia remains competitive in the digital economy.